Amchitka and the bomb : nuclear testing in Alaska - Kohlhoff, Dean. (Seattle, Wash. : University of Washington Press, 2002)
From 1965 through 1971, the US set off three underground atomic blasts in the remote wilderness of the Aleutian islands off the coast of Alaska. Detailing how these nuclear explosions were planned and conducted in spite of protests by political and civilian groups, this book traces the environmental impact of the blasts on the Aleutian wildlife refuge system and examines the social and political fallout from the tests on Aleut civilian populations.
Among the many islands -- On an anvil of war -- Before a mighty windstorm -- Nuclear Alaska -- Under Rufus & Larkspur Scrutiny -- During a long shot -- Through Milrow calibration -- Safeguard security -- Amid more Cannikin controversy -- Beyond the last bomb.
Includes bibliographical references (pages 118-156) and index.
Print version record.
English.
JSTOR
Keywords: Nuclear weapons -- Alaska -- Amchitka Island -- Testing; Nuclear weapons -- Testing -- Environmental aspects -- Alaska -- Amchitka Island; United States -- Politics and government -- 1945-1989.; Amchitka Island (Alaska) -- History -- 20th century; Armes nucléaires -- Alaska -- Amchitka -- Essais; Armes nucléaires -- Essais -- Aspect de l'environnement -- Alaska -- Amchitka; États-Unis -- Politique et gouvernement -- 1945-1989.; Amchitka (Alaska) -- Histoire -- 20e siècle.; HEALTH & FITNESS -- Safety; HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Nuclear weapons -- Testing; Nuclear weapons -- Testing -- Environmental aspects; Politics and government; Alaska -- Amchitka Island; United States; Kernwaffentest; Politik; Radioaktiver Niederschlag; Umwelt; Amchitka Island; Alaska; USA; Geschichte 1965-1971.; Geschichte 1945-1989.; 1900-1999; History